DETERMINANTS OF INTELLECTUAL CAPITAL DISCLOSURE IN THE BANKING SECTOR: THE ROLE OF PROFITABILITY, LEVERAGE, AND BOARD INDEPENDENCE - Muhammad Rivandi; Bella Okta Sari; Dewi Zulvia; Elsa Meirina (UIN MAHMUD YUNUS BATUSANGKAR, 2026)
Intellectual Capital Disclosure refers to the disclosure of information related to a company’s intellectual capital presented in annual reports or financial statements as a form of transparency to stakeholders. Intellectual capital itself represents intangible assets that serve as a source of competitive advantage in the knowledge-based economy. The purpose of this study is to empirically examine the significant effects of profitability, leverage, and independent commissioners on intellectual capital disclosure in banking sub-sector companies during the 2022–2024 period. This research employs a quantitative approach, and the sampling technique used is purposive sampling. The study includes 36 companies observed over a three-year period, resulting in a total of 108 observations. The data were obtained from the Indonesia Stock Exchange (IDX) https://www.idx.co.id/id and the respective companies’ official websites. Data processing was conducted using E-Views version 12, and the analysis method applied was panel data regression. The results of this study indicate that profitability has a positive effect on intellectual capital disclosure, while leverage and independent commissioners have no significant effect on intellectual capital disclosure.